Analisa Manajemen Support dalam Manajemen Obat di Unit Farmasi Rumah Sakit Universitas Indonesia - Afiyani, Nadia; Suwandi, Indah Pratiwi; Andriani, Helen (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Management support in the Pharmacy Unit aims to support medication management in order to achieve more optimal results, which consist of organization management, human resources management, administration and finance management, and system information management. This study aims to determine the condition of management support in drug management at the University of Indonesia Hospital Pharmacy Unit.This research was conducted in an observational manner with descriptive analysis related to support management. The data were obtained qualitatively through interviews with the Head of the Pharmacy Unit at UI Hospital. The results of research at the UI Hospital Pharmacy Unit show that the Human Capital problem is related to the lack of human resources in the Pharmacy Unit so it has an impact on the duration of service and employee welfare. In Organizational Capital it is known that the organizational culture created in the Pharmaceutical Unit is very good, by focusing on prudence, thoroughness, and communication. In addition, the relatively young age of HR is also an added value in the spirit of learning new things at Information Capital, because this speed of adaptation greatly supports the use of SIMRS. In financial management, spending or pharmaceutical spending is not the biggest expense, even so, planning and control must be carried out properly to prevent losses. Management support at the UI Hospital Pharmacy Unit has been going quite well. In the future, it is hoped that there will be an increase in the number of human resources to adjust the workload with pharmaceutical services that run more optimally and maintain employee welfare. The culture of a good work environment must be monitored considering that many fresh graduate employees are expected to create a comfortable and conducive work environment for work and study. Keywords: Support Management, Drug Management, Pharmacy Units, Hospitals  ABSTRAK Manajemen support (manajemen pendukung) di Unit Farmasi bertujuan untuk mendukung manajemen obat agar dapat mencapai hasil yang lebih optimal yang terdiri dari organization management, human resources management, administration and finance management, dan system information management. Penelitian ini bertujuan untuk mengetahui kondisi pada manajemen support dalam manajemen obat di Unit Farmasi Rumah Sakit Universitas Indonesia. Penelitian ini dilakukan secara observasional dengan analisa deskriptif terkait manajemen support, data diperoleh secara kualitatif melalui wawancara dengan Kepala Unit Farmasi RS UI. Hasil penelitian di Unit Farmasi RS UI menunjukan bahwa permasalahan Human Capital adalah terkait kurangnya SDM pada Unit Farmasi sehingga berdampak pada durasi pelayanan serta kesejahteraan pegawai. Pada Organizational Capital diketahui bahwa budaya organisasi yang tercipta di Unit Farmasi sudah sangat baik, dengan berfokus pada kehati-hatian, ketelitian, dan komunikasi. Selain itu usia SDM yang relatif masih muda juga menjadi nilai tambah dalam semangat mempelajari hal baru pada Information Capital, karena kecepatan beradaptasi ini sangat mendukung penggunaan SIMRS. Pada manajemen keuangan pengeluaran atau belanja farmasi bukan menjadi pengeluaran yang terbesar, meskipun begitu perencanaan dan pengendalian harus tetap dijalankan dengan baik untuk mencegah timbulnya kerugian. Manajemen support pada Unit Farmasi RS UI sudah berjalan dengan cukup baik. Kedepannya diharapkan adanya peningkatan jumlah SDM untuk menyesuaikan beban kerja dengan pelayanan kefarmasian yang berjalan lebih optimal dan menjaga kesejahteraan pegawai. Budaya pada lingkungan kerja yang baik harus diawasi mengingat banyak pegawai fresh graduate, diharapkan tercipta lingkungan kerja yang nyaman dan kondusif untuk bekerja dan belajar. Kata Kunci: Manajemen Support, Manajemen Obat, Unit Farmasi, Rumah Sakit